A study regarding bovine enterovirus type 1 infection in domestic animals and humans: An evaluation from the zoonotic aspect - Gur, Sibel; Gurcay, Metin; Seyrek, Adnan (Japan Soc Vet Sci, 2019)
Bovine enteroviruses (BEV) are members of Enterovirus genus of the family Picornaviridae. BEV1 has a broad host spectrum, including humans. The virus usually causes subclinical infection, but fatal/severe cases have also been reported in different animal species. There is quite limited data regarding BEV1 in humans. The purpose of this study is to investigate human infection and to identify possible risk factors for viral exposure. For this purpose, blood serum samples (n=1,526) were collected from a city center and nearby villagers simultaneously from humans and farm animals in Elazig province in Eastern Anatolia. As a result of serum neutralisation test, BEV1 specific antibody presence detected in cattle was 85.3% (163/191), 73.5% in donkeys (64/87), 71.8% in goats (115/160), 46.5% in sheep (93/200), 43.9% in horses (40/91), 41.3% in dogs (19/46) and 33% in humans (248/751). Although a high contamination potential was mentioned for people living in rural areas, it was determined that infection rates in rural areas (31.6%) and urban centers (32.2%) were very close. There was no difference according to sex. Viral exposure is higher in the 40 to 70 age range. In addition, the serological evidence of the infection in donkeys was identified for the first time with this study.
Keywords: bovine enterovirus type 1; human; seroprevalence; zoonosis